Ecologia de saberes: da decolonialidade à formação do sujeito ecológico no território quilombola Brejão dos Negros, Sergipe - Santos, Marcio Eric Figueira dos (2022)
Faced with the numerous colonial violence of epistemic, ontological, and economic bases originated in the paradigm of modernity and that culminates in the socio-environmental crisis, racism (structural/environmental), exploitation, expropriation, inequality and social fascism, erasure and devaluation of histories, knowledge/skills, identities, traditional cosmovisions and dissociation between human beings and nature, understanding and weaving paths from a participatory diagnosis and a Critical/Decolonial Environmental Education that helps in the valorization and/or construction of a decolonial ecosystem for the good living in the territories becomes the way to establish an ecological ideal, interculturality, democracy, and cognitive and social justice. The research developed in the Master Program in National Network for Teaching Environmental Sciences - PROFCIAMB, entitled "Ecology of Knowledge: from decoloniality to the formation of the ecological subject in the quilombola territory Brejão dos Negros, Sergipe", had as participants 29 people from the 30 vacancies available for the age group between 12 and 80 years old from the Santa Cruz community, located in the quilombola territory Brejão dos Negros (Brejo Grande - SE). Based on the entire methodology from the alliance between Post-Structuralism, Action Research, and Project-Based Learning, it aims to understand territorial dynamics, traditional knowledge, and aspects of the multifunctionality of peasant agriculture in the Santa Cruz Community in the light of decoloniality and propose solutions or proposals for socio-environmental problems, impacts and/or injustices, resulting in the EcoGuardiões da Comunidade app and artifacts produced by the participants. It is observed in the quilt of results that it was possible to help in the process of sensitization/awareness of the subjects and to obtain in the process of learning and local diagnosis from the characterization of the study area, the socio-environmental, productive, ethnobotanical and economic specificities, to the needs and potentialities of Community-Based Tourism, relevant to the multifunctionality of peasant agriculture. As well as indicating, idealizing and building solutions or proposals for socio-environmental problems, impacts and/or injustices, having as the outcome, in addition to the app, the demonstration against environmental racism by ExxonMobil in the territory and a podcast aimed at debating and disseminating the potential of the Community-Based Tourism and the debate and denunciation of threats and socioenvironmental impacts in the region, the first episode focusing on environmental racism by ExxonMobil.